Inclinations in Studies into Multicultural Education in Turkey: A Content Analysis Study - Gunay, Rafet; Aydin, Hasan (TURKISH EDUCATION ASSOC, 2015)
This study involves a content analysis of studies conducted in the field of multicultural education by researchers in Turkey. For this purpose, 32 research studies obtained in full-text from the ERIC database and the National Thesis Center of Turkey between 2005 and 2014 in addition to 7 published books are examined herein. In order to evaluate the related publications in terms of several variables, a content analysis coding method is used and all data regarding these publications are registered /recorded on a database. The data obtained from this database are analyzed using the SPSS 20.0 program. The results are presented descriptively in the form of graphics, frequencies and percentages. As a result of the study, it is seen that studies conducted on multicultural education in Turkey date back to nearly ten years ago, that the studies have increased in number starting from the year 2009, and that quantitative studies are preferred more frequently, that attitude scales are used as a data collection tool, that the population of the studies are mostly included by students and academicians and that the average population range is between 101 and 300, that research fields generally involved attitude studies as opposed to multicultural approaches, that three different types of data collection tools are used in these studies that ANOVA is employed as a data analysis method and that the use of central tendency scales, percentages and frequency tables is given utmost importance. As the first content analysis study in its field, this study advises the use of different analysis methods in line with current analyses, an increase in sample size, an increase and enrichment in method and application samples and the forming of constructive hypotheses to ensure appropriate quality studies that are in line with goals.
Keywords: Multicultural Education in Turkey; Research fields; Scientific publications; Content analysis; Education & Educational Research